Time‐dependent traction force microscopy for cancer cells as a measure of invasiveness. Issue 4 (25th March 2013) - Peschetola, Valentina; Laurent, Valérie M.; Duperray, Alain; Michel, Richard; Ambrosi, Davide; Preziosi, Luigi; Verdier, Claude
<x xml:space="preserve">Abstract</x> The migration of tumor cells of different degrees of invasivity is studied, on the basis of the traction forces exerted in time on soft substrates (Young modulus ∼ 10 kPa). It is found that the outliers of the traction stresses can be an effective indicator to distinguish cancer cell lines of different invasiveness. Here, we test two different epithelial bladder cancer cell lines, one invasive (T24), and a less invasive one (RT112). Invasive cancer cells move in a nearly periodic motion, with peaks in velocity corresponding to higher traction forces exerted on the substrate, whereas less invasive cells develop traction stresses almost constant in time. The dynamics of focal adhesions (FAs) as well as cytoskeleton features reveals that different mechanisms are activated to migrate: T24 cells show an interconnected cytoskeleton linked to mature adhesion sites, leading to small traction stresses, whereas less invasive cells (RT112) show a less‐structured cytoskeleton and unmature adhesions corresponding to higher traction stresses. Migration velocities are smaller in the case of less invasive cells. The mean squared displacement shows super‐diffusive motion in both cases with higher exponent for the more invasive cancer cells. Further correlations between traction forces and the actin cytoskeleton reveal an unexpected pattern of a large actin rim at the RT112 cell edge where higher forces are colocalized, whereas a more usual cytoskeleton structure with stress fibers and FAs are found for T24 cancer cells. We conjecture that this kind of analysis can be useful to classify cancer cell invasiveness. © 2013 Wiley Periodicals, Inc.